Simple object-oriented design - Aniche, Maurício (Manning Publications, 2024)
Simple object-oriented design: Create clean, maintainable applications presents practical design principles you can use to keep an object-oriented codebase simple as it grows and changes. Written as a collection of practical techniques you can apply in any OO language, it offers tips for concise code, managing dependencies and modules, and designing flexible abstractions. Illuminating figures, real-world examples, and insightful exercises make each principle stick.
"In Video Editions the narrator reads the book while the content, figures, code listings, diagrams, and text appear on the screen. Like an audiobook that you can also watch as a video.". - Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Object-oriented programming (Computer science); Programmation orientée objet (Informatique); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet